GeoSpatial Semantics Third International Conference, GeoS 2009, Mexico City, Mexico, December 3-4, 2009. Proceedings - Janowicz, Krzysztof; Raubal, Martin; Levashkin, Sergei; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book constitutes the refereed proceedings of the Third International Conference on GeoSpatial Semantics, GeoS 2009, held in Mexico City, Mexico in December 2009. The 10 revised full papers presented together with 2 keynote speeches were carefully reviewed and selected from 19 submissions. The papers are organized in topical sections foundations on geo-semantics; formal representation of geospatial data; semantics-based information retrieval and recommmender systems; integration of sematics into spatial query processing; and geo-ontologies and applications.
Keynotes -- Multi-cultural Aspects of Spatial Knowledge -- Towards Reasoning Pragmatics -- Foundations of Geo-semantics -- A Functional Ontology of Observation and Measurement -- The Case for Grounding Databases -- Formal Representation of Geospatial Data -- Towards a Semantic Representation of Raster Spatial Data -- Bottom-Up Gazetteers: Learning from the Implicit Semantics of Geotags -- Semantics-Based Information Retrieval and Recommender Systems -- Ontology-Based Integration of Sensor Web Services in Disaster Management -- A Spatial User Similarity Measure for Geographic Recommender Systems -- Integration of Semantics into Spatial Query Processing -- SPARQL Query Re-writing Using Partonomy Based Transformation Rules -- iRank: Ranking Geographical Information by Conceptual, Geographic and Topologic Similarity -- Geo-ontologies and Applications -- Towards an Ontology for Reef Islands -- Narrative Geospatial Knowledge in Ethnographies: Representation and Reasoning.
Keywords: Computer science; Earth sciences; Database management; Data mining; Information storage and retrieval; Artificial intelligence; Computer Science; Information Storage and Retrieval; Earth Sciences, general; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery; Database Management; Electronic books